Photocatalytic Oxidative Heterocyclization of Semicarbazones: An Efficient Approach for the Synthesis of 1,3,4-Oxadiazoles - Kapoorr, Ritu; Singh, Sachchida N.; Tripathi, Shubhangi; Yadav, Lal Dhar S. (Synlett, 2015)
A highly efficient eosin Y catalyzed oxidative heterocyclization of semicarbazones was established under visible-light photoredox catalysis using CBr4 as a bromine source. The protocol renders a rapid, mild, and efficient access to valuable 5-substituted 2-amino-1,3,4-oxadiazoles in an operationally simple way utilizing visible light and atmospheric oxygen.
Keywords: visible light; eosin Y; photoredox catalysis; 1,3,4-oxadiazole; oxidative heterocyclization